The Interplay of Intrinsic and Extrinsic Motivations with Challenges and Learning Preferences among Iraqi EFL University Students Enrolling in English Departments - Mohammed, Adyan Abdulmunim (Randwick International of Education and Linguistics Science Journal, 2024)
The aim of this study is to investigate the motivation of the Iraqi EFL students, the factors that discourage their pursuing of the language studies and the available options that the Iraqi students consider in learning the language. A questionnaire was conducted to 124 EFL students enrolled in the Department of English at the College of Education/University of Kufa. The results revealed students are strongly dependent on extrinsic motivation that comes from the pre-university level educational experience. The most important extrinsic motivation that propels the students to study English is improving the job opportunities in the market along with improving the academic options in the post graduate level. The result also shows that intrinsic motivation such as the student' interest in the English culture and literature have less effect on their learning motivation. Additionally, the study designates some challenges that impede the learning process, including limited exposure to English outside the classroom, issues within the educational system and socioeconomic factors that hinder students' learning. Furthermore, the research highlights the importance of teacher-student dynamics. In terms of learning preferences, the students are interested in interactive and multimedia resources in addition to traditional classroom experience. The paper offers some recommendations for enhancing student's motivation and engagement through targeted interventions, such as incorporating practical applications, extracurricular activities, and access to digital resources. These findings contribute to the understanding of EFL education in Iraq and offer insights for teachers and policymakers aiming to improve English language learning outcomes in the region.